Strengthening of existing composite steel-concrete beams utilising bolted shear connectors and welded studs. (November 2015) - Pathirana, Sameera Wijesiri; Uy, Brian; Mirza, Olivia; Zhu, Xinqun
Abstract: This paper considers the flexural behaviour of steel-concrete composite beams retrofitted with two types of bolted connectors and welded stud connectors. Three composite beams, one from each connector type, and four non-composite beams were cast together. Three of the non-composite beams were retrofitted using the three connector types respectively. The connectors were installed through holes cored in the concrete slabs of the beams. The holes were backfilled using structural grout. The beams were then tested under static flexural loading. The load-slip behaviour of these connectors under normal and retrofitted conditions was investigated using push-tests. The flexural behaviour of the retrofitted beams was compared with that of the normal composite beams and non-composite beams. The ultimate loads of the test specimens were compared with the design ultimate loads of these beams calculated using Rigid Plastic Analysis (RPA). The vertical deflection of the beams under serviceable load regimes was also compared. The beam experiments were simulated using Finite Element (FE) models developed with ABAQUS. Material models with damage parameters were specified for the concrete and grout used in the test specimens using the Concrete Damage Plasticity (CDP) option. The effects of the concrete and grout strength, grout-hole size and shear connection ratio on the flexural behaviour of retrofitted beams were investigated by carrying out a parametric analysis. The results obtained from full-scale beam and push-test experiments and also the analytical results from RPA and FE analyses are presented and discussed in detail in this paper. Highlights: Feasibility of utilising blind bolt connectors in retrofitting of steel-concrete composite beams was investigated. Bolted connectors demonstrated much higher shear capacity than the welded stud connectors in both the normal and retrofitted conditions. The existing non-composite beams were feasibly retrofitted utilising the bolts. The strength of a non-composite beam was increased by approximately 40% by using the BB2 connectors. The capacity of the retrofitted beams is increased with the concrete strength and it is not considerably influenced by the grout strength or the grout-hole size.